2009
DOI: 10.1007/s11689-009-9009-8
|View full text |Cite
|
Sign up to set email alerts
|

Teasing apart the heterogeneity of autism: Same behavior, different brains in toddlers with fragile X syndrome and autism

Abstract: To examine brain volumes in substructures associated with the behavioral features of children with FXS compared to children with idiopathic autism and controls. A cross-sectional study of brain substructures was conducted at the first time-point as part of an ongoing longitudinal MRI study of brain development in FXS. The study included 52 boys between 18–42 months of age with FXS and 118 comparison children (boys with autism-non FXS, developmental-delay, and typical development). Children with FXS and autisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 52 publications
8
105
1
Order By: Relevance
“…Hoeft et al [78] and Meguid et al [79] have reported differences in the direction of morphologic abnormalities in the two types of ASD. Individuals with FXS, with or without ASD, have a larger caudate nucleus and smaller amygdala than their counterparts with idiopathic ASD [80]. Although these distinctions could be accounted for by methodological issues, they support the notion that ASD is a neurobiologically heterogeneous behavioral syndrome [81].…”
Section: Neurobiological Correlates Of Asd In Fxs: Anomalies Of the Cmentioning
confidence: 97%
“…Hoeft et al [78] and Meguid et al [79] have reported differences in the direction of morphologic abnormalities in the two types of ASD. Individuals with FXS, with or without ASD, have a larger caudate nucleus and smaller amygdala than their counterparts with idiopathic ASD [80]. Although these distinctions could be accounted for by methodological issues, they support the notion that ASD is a neurobiologically heterogeneous behavioral syndrome [81].…”
Section: Neurobiological Correlates Of Asd In Fxs: Anomalies Of the Cmentioning
confidence: 97%
“…The most replicated findings to date include increased volume of the caudate nucleus [134][135][136][137][138][139][140] and reduced volume of the cerebellum [136,141,142] compared to both healthy comparison groups and those with ASD. Other findings noted in some studies include increased volume of the lateral ventricles [135,143,144]; hippocampus [145][146][147]; parietal lobes [136,139], and brainstem [139] and reduced volume of the cerebellar vermis [141].…”
Section: Full Mutation Fraxmentioning
confidence: 98%
“…Several studies have analyzed how hippocampal volume changes in FXS using a variety of techniques. Some studies have reported an increase in hippocampal volume (Reiss et al, 1994, Kates et al, 1997, Hazlett et al, 2009, one has reported a decrease (Hoeft et al, 2008), while others have found no change in hippocampal volume (Jakala et al, 1997. While it is difficult to obtain a consensus from the studies to date, it is likely that these discrepancies arise from a number of factors that include small sample sizes as well as differences in the age, sex, and number of CGG repeats among patients studied.…”
Section: Hippocampal Neuropathology In Fxs Patientsmentioning
confidence: 99%